Da atividade à invalidez permanente: um estudo utilizando dados do Regime Geral da Previdência Social (RGPS) - Marilia Miranda Forte Gomes (2008)
The main goal of this masters thesis is to estimate a Disability Beneficiaries Life Table from the General Social Security Regime for Private Sector Workers (RGPS), by sex and age, based on the 1999 and 2002 registries. The probabilities of withdraw by permanent disability are essential for the construction of this table. The probabilities were estimated as a function of the smoothed permanent disability rates. The probabilities were estimated by age and sex, and results were compared to the main tables used by the social security market. The results show that in contradiction with the disability life tables used in the private sector that male disability retirement hazard, increases steadly until age 65 and after that it decreases. However, for females, these risks increase continuously up to the oldest age. The results can be explained by the configuration of the public pension system in Brazil. The system offers different possibilities of retirement benefits at the same time, thus turning the benefits competitive among each other. In addition to that, the decline in the probabilities of retirement after age 65 indicates that individuals who are still in the labor force beyond this age belong to a very specific group of the population, normally characterized by better health conditions. A second possible explanation is that individuals in bad health condition retired from the labor force using one of the several retirement benefits offered by the public social security system. The estimated disability life table also seems to be adequated to a pension system with a large number of participants. Therefore, this thesis contributes to a better understanding of work and disability, especially in the field of social security and retirement.